Ammonium across a Selective Polymer Inclusion Membrane: Characterization, Transport, and Selectivity. Issue 10 (8th April 2016) - Casadellà, Anna; Schaetzle, Olivier; Loos, Katja
Abstract : The recovery of ammonium from urine requires distinguishing and excluding sodium and potassium. A polymer inclusion membrane selective for ammonium is developed using an ionophore based on pyrazole substituted benzene. The interactions of the components are studied, as well as their effect on transport and selectivity. Spectroscopic and thermogravimetric measurements show no extensive physical interactions of the components, and that the plasticizer reduces the intermolecular forces (rigidity) of the membrane. The ionophore turns the membrane more rigid, although it increases its swelling degree and therefore the affinity of cations. A ratio of plasticizer (DEHP) and polymer (PVC) of 1:3 in mass gives the highest ammonium flux. Tested contents of ionophore (2 and 5 wt%) show that the higher the content of the ionophore, the fastest the flux is (7.5 × 10 −3 mmol cm −2 h −1 ). Selectivity of NH4 + over Na + and over K + is reduced from 13.07 to 9.33 and from 14.15 to 9.57 correspondingly. Abstract : Ammonium flux and its selectivity over potassium and sodium across a polymer inclusion membrane are affected by the composition of the membrane. Especially they are affected by the intermolecular interactions among the components. The addition of a pyrazole‐based ionophore does not add or reduce the intermolecular forces in polymeric matrix containing plasticizer, and it provides selectivity to the membrane.